Differences in gut microbiota composition of laying hen lines divergently selected on feather pecking. (21st June 2019) - van der Eijk, Jerine A J; de Vries, Hugo; Kjaer, Joergen B; Naguib, Marc; Kemp, Bas; Smidt, Hauke; Rodenburg, T Bas; Lammers, Aart
ABSTRACT: Feather pecking (FP), a damaging behavior where laying hens peck and pull at feathers of conspecifics, is multifactorial and has been linked to numerous behavioral and physiological characteristics. The gut microbiota has been shown to influence host behavior and physiology in many species, and could therefore affect the development of damaging behaviors, such as FP. Yet, it is unknown whether FP genotypes (high FP [HFP] and low FP [LFP] lines) or FP phenotypes (i.e., individuals differing in FP, feather peckers and neutrals) differ in their gut microbiota composition. Therefore, we identified mucosa-associated microbiota composition of the ileum and cecum at 10 and 30 wk of age. At 30 wk of age, we further identified luminal microbiota composition from combined content of the ileum, ceca, and colon. FP phenotypes could not be distinguished from each other in mucosa-associated or luminal microbiota composition. However, HFP neutrals were characterized by a higher relative abundance of genera of Clostridiales, but lower relative abundance of Lactobacillus for the luminal microbiota composition compared to LFP phenotypes. Furthermore, HFP neutrals had a higher diversity and evenness for the luminal microbiota compared to LFP phenotypes. FP genotypes could not be distinguished from each other in mucosa-associated microbiota composition. Yet, FP genotypes could be distinguished from each other in luminal microbiota composition. HFP birds were characterized by a higher relative abundance of genera of Clostridiales, but lower relative abundance of Staphylococcus and Lactobacillus compared to LFP birds. Furthermore, HFP birds had a higher diversity and evenness for both cecal mucosa-associated and luminal microbiota compared to LFP birds at adult age. In conclusion, we here show that divergent selection on FP can (in)directly affect luminal microbiota composition. Whether differences in microbiota composition are causal to FP or a consequence of FP remains to be elucidated.